Facilitators and Barriers to Health-Seeking Behaviours among Filipino Migrants: Inductive Analysis to Inform Health Promotion. (25th August 2015) - Maneze, D.; DiGiacomo, M.; Salamonson, Y.; Descallar, J.; Davidson, P. M.
Abstract : Understanding factors that influence health-seeking behaviour of migrants is necessary to intervene for behaviour change. This paper explores Filipino migrants' perceptions of facilitators and barriers to maintaining health in Australia. Open-ended survey item responses reflecting factors that assisted and hindered health following migration to Australia were inductively analysed. Three hundred and thirty-seven of the 552 survey respondents (61%) provided open-ended responses. Responses were grouped into two major categories: individual factors, including personal resources and cultural influences, and environmental factors encompassing both the physical conditions in the host country and health service access. Awareness of practices that enhance health was a major personal facilitator of health-seeking behaviour; however, competing priorities of daily living were perceived as barriers. Cultural beliefs and practices influenced health-seeking behaviour. Despite high self-rated English language skills in this population, new migrants and the elderly cited communication difficulties as barriers to accessing health services. Insight into facilitators and barriers to health-seeking behaviour in this less researched migrant population revealed tools for enhancing engagement in health promotion programs addressing healthy lifestyle.